'Ticagrelor alone vs. dual antiplatelet therapy from 1 month after drug-eluting coronary stenting among patients with STEMI': a post hoc analysis of the randomized GLOBAL LEADERS trial. Issue 7 (2nd July 2021) - Gamal, Amr S; Hara, Hironori; Tomaniak, Mariusz; Lunardi, Mattia; Gao, Chao; Ono, Masafumi; Kawashima, Hideyuki; Jüni, Peter; Vranckx, Pascal; Windecker, Stephan; Hamm, Christian; Steg, Philippe Gabriel; et al.
Abstract: Aim: To evaluate the efficacy and safety of ticagrelor monotherapy beyond 1 month and up to 24 months vs. standard 12-month dual antiplatelet therapy (DAPT) with aspirin and ticagrelor followed by aspirin monotherapy among ST-elevation myocardial infarction (STEMI) patients undergoing percutaneous coronary intervention (PCI) in the GLOBAL LEADERS trial. Methods and results: We performed a post hoc analysis of STEMI patients in the GLOBAL LEADERS trial comparing experimental ticagrelor monotherapy (1062 patients) with standard 12-month DAPT (1030 patients). We evaluated predefined primary and secondary endpoints in both treatment arms. Rates of net adverse clinical events (NACE), patient-oriented composite endpoints (POCE), and bleeding academic research consortium (BARC)-defined bleeding Type 3 or 5 were also evaluated. At 2 years, there were no significant differences in rates of primary endpoints in patients who had STEMI [0.89 (0.61–1.31)]. There were similar rates of NACE and POCE in both experimental and reference treatment groups at 2 years post-PCI [hazard ratio (HR) 0.96 (0.77–1.20) and 0.96 (0.77–1.21), respectively]. BARC 3 or 5 bleeding events were numerically less in experimental compared to reference treatment groups at 1 year [HR 0.55 (0.27–1.13)] and 2 years [0.61 (0.32–1.16)]. Conclusion: Presentation with STEMI has not influenced the incidence of GLOBAL LEADERS defined primary endpoints. There were no significant differences in rates of NACE, POCE, and BARC bleeding between the two treatment groups up to 2 years of follow-up. Although these findings should be viewed as exploratory, they expand the evidence on potential safety of aspirin-free antiplatelet strategies after PCI in STEMI.